Cinética de secagem de café natural para diferentes temperaturas e baixa umidade relativa - Alves, Guilherme Euripedes; Isquierdo, Eder Pedroza; Borém, Flávio Meira; Siqueira, Valdiney Cambuy; Oliveira, Pedro Damasceno [UNESP]; Andrade, Ednilton Tavares (My University, 2013)
In face of the importance of drying in the post-harvest phase of coffee and its effect on the final quality of the product, the aim of the present study was to evaluate drying kinetics at different temperatures of the drying air for a low dew point temperature of the fruits of dry processed Arabica coffee (Coffea arabica L.). The fruits were manually picked and subjected to hydraulic separation. After that, fruits with initial moisture contents of 1.9 ± 0.1 kg.kg-1 (db) were submitted to the drying process under three dry bulb temperatures (35°C, 40°C e 45°C) for the same dew point temperature (2.6°C) of the drying air. Seven mathematical models were fitted to the experimental data to characterize the drying process of the coffee fruit. The modified Henderson and Pabis and Successive Residue models with two terms were the most adequate for describing the dry process, with the modified Henderson and Pabis model being chosen through its greater simplicity. The increase of the dry bulb temperature under a low dew point temperature leads to an increase in the effective diffusivity coefficient and in the drying rate and a decrease in drying time. For the conditions studied, the effective diffusivity coefficient of water for coffee fruits ranges from 1.908 to 3.721 x 10-11 m2.s-1. Activating energy for liquid diffusion, described by the Arrhenius equation, was 52.89 kJ.mol-1.
Drying kinetics of natural coffee for different temperatures and low relative humidity
Keywords: Coffea arabica L; Drying rate; Mathematical modeling